Board diversity and firm performance: The role of business group affiliation. Issue 6 (December 2019) - Aggarwal, Raj; Jindal, Varun; Seth, Rama
Highlights: Prior literature documents inconsistent results on the board diversity–firm performance relationship, suggesting incomplete research designs with missing contextual variables. This study proposes business group affiliation as an important contextual factor and examines how it influences the relationship between board diversity and firm performance. Board demographic diversity has a positive (negative) association with Tobin's Q for standalone (group-affiliated) firms. The negative effect of group affiliation in the diversity-performance relationship is confirmed using the market reaction to the announcement of mergers and acquisitions. The findings indicate that business group affiliation impairs the positive firm value effects of board demographic diversity. Abstract: There is little consensus globally on the relationship between board diversity and firm performance. Using the resource dependence and agency views, this paper examines how business group affiliation influences the relationship between board diversity and firm performance as a contextual/confounding factor. Based on data for listed firms in India, we find that board demographic diversity is positively associated with the firm performance (Tobin's Q) of standalone firms, but this association is negative for group-affiliated firms. This negative effect of group affiliation is confirmed in a test based on a novel measure of firm performance using the stock market reaction to the announcement of mergers and acquisitions. For both measures of performance, we show that business group affiliation impairs the positive firm value effects of board demographic diversity. These findings imply that the relationship between board diversity and firm performance requires re-examination in the many countries where group affiliation is common. Our results also provide evidence of a new cost of group affiliation and show in a fresh context that cross-country studies should account for international variations in ownership and institutional structures.